Fungi the crucial contributors for nanotechnology: a green chemistry perspective - Moudgil, Aliesha; Chaudhari, Bhushan P. (Advancing Frontiers in Mycology & Mycotechnology, 2019)
Myconanotechnology has gained an exceptional momentum in today’s world. It encompasses a wide range of applications like in agriculture, biomedical, electronics, textiles, cell and molecular biology, nanodevices, and many more. This fast-growing research field has a list of many nanoparticles that have been synthesized from different kinds of fungi. It is an eco-friendly approach that has sidelined the conventional methods of chemical and physical synthesis that require high energy and are toxic and expensive. The fungal-based synthesis gains functionality due to its discrete and diversified advantages that are being explored. Various parameters like temperature, pH, time and concentrations of fungal biomass or extract as well as of the precursor play a vital role in the protocols. These factors have to be optimized for the laboratory as well as industrial scale production. A greater importance to the use of cell-free extracts for nanosynthesis has been given. They contain the enzymes that are reported to be involved in the synthesis mechanisms as reducing agents and capping agents. The role of fungi in nanosynthesis and nanotechnology per se has many patents under its name. Although there are voids in the existing synthesis methods as well as lacunae in the application part that need to be addressed and filled. With an extensive research and work, myconanoparticles can be exploited to the maximum and lead its advancement in new areas.

Functionalized gold nanorods (GNRs) as a label for the detection of thyroid-stimulating hormone (TSH) through lateral flow assay (LFA) - Varma, Sanjana; Burade, Dimpal K.; Chaudhari, Bhushan P. (Emergent Materials, 2025)
Thyroid-stimulating hormone (TSH) is an important biomarker of thyroid dysfunctions. Different types of nano biosensors have been developed to detect TSH. However, there is a lacuna in the development of sensitive paper-based nano biosensors due to less sensitivity and instability of the labels. Interestingly, the intense color and localized surface plasmon resonance (LSPR) property make gold nanorods (GNRs) an efficient lateral flow assay (LFA) label instead of spherical gold nanoparticles. The rapidity, simplicity and user-friendly functioning of LFAs make them a predominant technique compared to electrochemical techniques for point-of-care diagnosis. This proof-of-concept study underlines the role of stable GNRs as a novel label for LFAs. The TSH antibody functionalized GNRs can semi-quantitatively diagnose hyperthyroidism and hypothyroidism. The limit of detection (LOD) of the LFA is 0.3 µIU/mL, determined by visually analyzing the color development at the test line without employing any quantification method. Moreover, the study provides a comprehensive understanding of seed-mediated synthesis and functionalization of GNRs, which would benefit the researchers in suitably designing the GNRs-based labels for LFAs. Considering their exceptional characteristics, GNR-based LFAs are expected to surpass other labelling nanomaterials in detecting various biological markers. This enhanced sensitivity could significantly improve the clinical utility of diagnostic kits.